Actin assembly at sites of contact between the cortical ER and endocytic pits promotes ER autophagy. Issue 1 (2nd January 2023) - Liu, Dongmei; Ferro-Novick, Susan; Novick, Peter
ABSTRACT: A recent screen of the Saccharomyces cerevisiae deletion library implicated End3 in autophagy of the endoplasmic reticulum (ER). Together with Pan1, End3 coordinates endocytic site initiation with the localized assembly of branching actin filaments that promotes invagination of endocytic pits. Oxysterol binding proteins function as an inter-organelle bridge by interacting with VAP proteins on the cortical ER and type I myosins on the endocytic pit. These proteins not only promote localized actin assembly at contact sites, they are required for ER autophagy as well. We propose that localized actin polymerization can push the edge of an ER sheet from the cell cortex toward the site of autophagosome assembly near the vacuole.